Callus induction from various explants of French bean (Phaseolus vulgaris L.) - Sangle, V. A. Waghmare., N. B. Pandhure; V. S.Kothekar, S. E. Mahamune*, R. P. Bansode., S. M. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Callus cultures were studied in white seed induced mutant obtained from Phaseolus vulgarisL., cv. varunto help establish a suitable protocol for a prospective in vitro program. Callus cultures were initiated from the axillary leaves, axillary shoots, node, internode, and root segments.The initiation and growth of callus were evaluated on MS medium with 3% sucrose, 0.4% agar, 1.5 mg.l-1BAP, and three levels of IAA. The highest callus relative growth was obtained on medium with 0.5 mg.l-1IAA and 1.5 mg.l-1BAP.